2019
DOI: 10.3389/fnins.2019.00971
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Functional Connectivity of the Anterior Cingulate Cortex in Patients With Borderline Personality Disorder

Abstract: BackgroundEmerging evidences supported the hypothesis that emotional dysregulation results from aberrant connectivity within the fronto-limbic neural networks in patients with borderline personality disorder (BPD). Considering its important role in emotional regulation, the anterior cingulate cortex (ACC) has not yet been fully explored in BPD patients. Therefore, using the seed-based resting state functional connectivity (rsFC) and probabilistic fiber tracking, we aimed to explore the alterations of functiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 71 publications
(81 reference statements)
1
12
0
Order By: Relevance
“…Resting-state FC, focusing on the statistical correlation between signals in the whole brain or regional brain areas ( Fox and Raichle, 2007 ), has shown substantial clinical research potential for exploring synchronous brain activity, which is also the highlight of the current research. Region-of-interest (ROI) studies based on resting-state FC have been considered sensitive and reliable ( Hampson et al, 2002 ), and these techniques have been widely applied in various objective analyses of brain functional activity, varying from sleep disorders to neuropsychiatric diseases ( Lei et al, 2019 ; Guo et al, 2020 ). Thus, resting-state FC studies based on ROI may be incredibly useful in evaluating insular FC integrity in patients with OSA.…”
Section: Introductionmentioning
confidence: 99%
“…Resting-state FC, focusing on the statistical correlation between signals in the whole brain or regional brain areas ( Fox and Raichle, 2007 ), has shown substantial clinical research potential for exploring synchronous brain activity, which is also the highlight of the current research. Region-of-interest (ROI) studies based on resting-state FC have been considered sensitive and reliable ( Hampson et al, 2002 ), and these techniques have been widely applied in various objective analyses of brain functional activity, varying from sleep disorders to neuropsychiatric diseases ( Lei et al, 2019 ; Guo et al, 2020 ). Thus, resting-state FC studies based on ROI may be incredibly useful in evaluating insular FC integrity in patients with OSA.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have reported that patients with MDD had a 2%-12% lifetime risk of dying by suicide (4,5), and the new study reported that the rated of suicide attempts (SA) was greater 4.78% in MDD by assessments of 3,284 adults with/without suicidal acts (6). Therefore, finding neurological features relating to SA in MDD patients could be a major achievement in preventing suicidal behavior (7).…”
Section: Introductionmentioning
confidence: 99%
“…113 The altered processing of fearful stimuli may also clarify why persons with BPD have a heightened fear of abandonment and instability when compared to persons without BPD. 114 BPD-rs-4, 115 BPD-rs-6, 116 and BPD-rs-7 117 highlight aberrations in FC of the ACC. The ACC is involved in various cognitive processes, such as motivation, decision making, emotion processing, learning, and conflict and error monitoring.…”
Section: Bpd Resting-state Summarymentioning
confidence: 99%